The Fate of Political Scientists in Europe From Myth to Action - Capano, Giliberto; Verzichelli, Luca (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
The Fate of Political Scientists in Europe not only draws a comprehensive picture of today's political science and of its scholars, but also reflects in a refreshing and challenging way on what it should be. - Kris Deschouwer, Emeritus Professor, Vrije Universiteit Brussels, Belgium. Giliberto Capano and Luca Verzichelli take us into a fascinating intellectual journey that sheds light on how European scholars conceive of the profession and what attitudes and values animate their research activities. - Manuela Moschella, Associate professor in Political Science, Scuola Normale Superiore, Pisa, Italy. Every so often academic disciplines should take stock of where they have come from, what they are, and what they want to be. This thorough study of European political science is an excellent example of such a stock-taking. - B. Guy Peters, Maurice Falk Professor of American Government, University of Pittsburgh, USA. This open access book offers a systematic survey of the attitudes and values of European political scientists. It builds a structural interpretation based on empirical data, as well as offering reflections on the future structure of the discipline. In the middle of a delicate phase of changes marked by the effects of pandemic and the war in Ukraine, we need to pay attention to the factors that are affecting not only the 'objects' of Political Science as a discipline but also its interactions with the world around it. First, this book asks to what extent the work of European political scientists is impacted by the current change. Second, their attitudes and predisposition about the future goals of the discipline are analysed. In the final chapter, the authors seek to understand to what extent a diffuse but still not completely institutionalized academic discipline will be able to produce a comprehensive impact around the European society, in order to be more visible and effective in policy making and policy processes. Giliberto Capano is Professor of Political Science and Public Policy at the University of Bologna, Italy. Luca Verzichelli is Professor of Political Science at the University of Siena, Italy.